THE STRUCTURE OF ENGLISH VOCABULARIES - Feruza Kucharova Alisher kizi; Usmonova Sabrina Siroj kizi (TADQIQOTLAR, 2025)
Abstract: English vocabulary is a rich and complex system that has evolved over centuries, influenced by various languages and cultures. Its structure is built upon several  fundamental  elements,  including  word  formation,  borrowing,  and  semantic relationships, each contributing to its vast lexicon and dynamic usage.